Effects of Islamic credit cards on customer spending - Idris, Umar Muhammed (s.n, 2013)
This perhaps better disseminate the attitude of Malaysian credit card holder towards spending and settlement behavior. In wake of this excessive burden of debt accumulating the Malaysian economy, it is an attempt to provide the effect of Islamic credit to the spending behavior of consumers. While Islamic banking practice peak to grow in Malaysia as to diversify their products to cater the need of the consumer, Islamic credit is also seen as an alternative catering the same purpose like conventional credit card with the due consideration of avoiding riba in the transaction